(untitled) (Journal of Partial Differential Equations, 2020)
" We consider the equation u_t = Tr[B(x, t, Du, 03a6u)D00b2u] + F(x, t, u, Du, 03a6u, 03c8u) where 03a6 and 03c8 are vector-valued mappings. We obtain the existence and uniqueness of classical solution to the equation for a 2208- periodic initial data. The problem is naturally arisen from image denoising."